An investigation of professional learning in dynamic environments - Bolt, Susan J (Curtin University, 2009)
Typically, individuals and managers of organisations seek to sustain competitive advantage and maximise their potential through participation in training and development. Prior to this study, little was known about the specific nature of the relationship between training and development and organisational change in the participating organisations. The purpose of this research was to investigate, describe and evaluate this relationship in a volunteer organisation and two government agencies in Australian contexts. So, the researcher investigated adult learning within three organisations in order to understand participants’ experiences with professional learning in a context of organisational change. As a result of this study the researcher made recommendations and developed a model that informs professional learning in dynamic environments.This research was situated within the interpretive paradigm and data were collected using multiple methods. Data collection involved 210 questionnaires and 70 semistructured interviews conducted across the three participating organisations. Quantitative questionnaire data were analysed using SPSS: Qualitative data from the questionnaires and interviews were entered into NVivo 7 and subsequently analysed with themes and categories identified. The major themes were provision, accessibility, motivation, effectiveness and relationship; the themes related directly to the research questions. Individual case reports were sent to managers in the participating organisations. The results are reported in the thesis as separate case studies and include the perspectives of both managers’ and non-managers’ experiences of training and development and its relationship to organisational change. Additionally, a cross-case analysis was conducted and discussed in relation to the literature reviewed in the thesis.Primarily, the researcher found that there were direct and indirect links between training and development and the organisational change agenda, but participants were not always aware of these relationships. Typically, managers provided formal learning opportunities for staff but overlooked the benefits of informal learning. In practice, participants used formal education, non-formal programs, informal and incidental learning; they recognised the benefits of informal and incidental learning. In this research, middle managers had difficulty accessing role-related training and development; managers and non-managers sought their own career development and job-related training and development beyond what was provided by their employers. Individuals’ motivation to participate in training and development was influenced by its relevance to their careers, jobs, and interests. Their motivation to transfer what they had learned into practice in the workplace depended on the purpose of the learning and opportunities for its implementation. Also, it was found that program evaluation was inconsistent and evaluation of staff training and development was marginalised.As a result of the findings, the researcher developed the ‘Integrative Model: Professional Learning in Dynamic Environments (IMPLIDE)’; comprised of three components - capacity, process, and approach. A key feature of IMPLIDE was the up skilling of managers and human resource developers to facilitate effective training and development programs. The findings of this research and the subsequent development of this model have significance for academics and practitioners in the field of human resource development. As a consequence of this research, areas for further research have been identified, particularly, in relation to the current capacity and professional development of middle managers.